Sustainable Warehouse Management Systems: Integrating Environmental and Social Responsibility in Supply Chain Operations - Parthiban Mohanasundaram (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative potential of Warehouse Management Systems (WMS) in driving environmental and social sustainability throughout Supply Chain operations. The article examines how modern WMS platforms have evolved beyond basic inventory control to become sophisticated enablers of sustainability initiatives, integrating advanced technologies such as artificial intelligence, Internet of Things sensors, and blockchain to optimize resource utilization while enhancing social responsibility. Through analysis of current research and industry implementations, the article presents a structured framework for sustainable warehouse management, addressing environmental considerations through inventory optimization, energy management, transportation efficiency alongside social dimensions, including ethical labor practices, responsible sourcing, and transparency mechanisms. The technical architecture, implementation strategies, and change management considerations are thoroughly examined for successful deployment, emphasizing the importance of comprehensive performance metrics and seamless integration with existing infrastructure. Looking toward future developments, the paper discusses emerging technologies like quantum computing and the increasing integration of circular economy principles, providing organizations with a roadmap for transforming conventional warehouse operations into intelligent, sustainability-optimized environments that deliver both ecological benefits and business value.
Keywords: Sustainable Warehouse Management; Supply Chain Sustainability; Environmental Technology Integration; Ethical Supply Chain; cular Economy Implementation